Detailed Reaction Mechanism of Phenylboronic Acid with Alizarin Red S in Aqueous Solution: Re‐Investigation with Spectrophotometry and Fluorometry. Issue 10 (3rd April 2017) - Suzuki, Yota; Sugaya, Tomoaki; Iwatsuki, Satoshi; Inamo, Masahiko; Takagi, Hideo D.; Odani, Akira; Ishihara, Koji
Abstract: Re‐investigation of the reaction of phenylboronic acid (PhB(OH)2 ) with Alizarin Red S (ARS, H2 L) was carried out using absorption and emission spectrophotometry to correct the currently proposed mechanism. Kinetic results obtained by both methods, which essentially show no significant differences, showed that the kinetic reactivity of ARS toward PhB(OH)2 was in the order H2 L < HL – and that of phenylboronic acid toward HL – was PhB(OH)2 > PhB(OH)3 – . Acetic acid/acetate buffer accelerated the present reaction, though HEPES buffer did not. A detailed reaction mechanism involving the acceleration effect of the acetate buffer is proposed for the present reaction on the basis of a recent universal reaction mechanism. Abstract : The reaction mechanism of phenylboronic acid with Alizarin Red S was fully reinvestigated; the reaction proceeded via 3 parallel pathways to form only the cyclic boronate ester in aqueous solution. In the acetic acid/acetate buffer solution, the reaction rate was accelerated by the outer‐sphere complex formation between the trigonal phenylboronic acid and acetate ion. A detailed reaction mechanism involving the acceleration effect of the acetate buffer was proposed for the present reaction on the basis of a recent universal reaction mechanism.